Shakespeare without women : representing gender and race on the Renaissance stage - Callaghan, Dympna (Accents on Shakespeare., 2000)
"Shakespeare Without Women is a controversial study of female impersonation and the connections between dramatic and political representation in Shakespeare's plays. In this book, Callaghan argues that all Shakespeare's actors were, of historical necessity, (white) males which meant that the portayal of women and racial others posed unique problems for his theatre. What is important, Shakespeare Without Women claims, is not to bemoan the absence of women, Africans, or the Irish, but to determine what such absences meant in their historical context and why they matter today."--Jacket